The effectiveness of kindergarten programs wich aim at preventing reading and spelling problems in school: A comparison of three different approaches - Roth, Ellen; Schneider, Wolfgang (Psychology: the Journal of the Hellenic Psychological Society, 2020)
ABSTRACT IS AVAILABLE IN THE PDF